Post-Pandemic Prevalence and Distribution of Refractive Errors in Balinese Schoolchildren: A Cross-Sectional Analysis - Dharmi Lestari, Ni Putu; Ariesanti Tri Handayani; Anak Agung Mas Putrawati Triningrat (HM Publisher, 2025)
Background: Uncorrected refractive errors are a leading cause of preventable visual impairment in children worldwide, impacting academic and social development. The COVID-19 pandemic disrupted routine pediatric eye health services and altered children's lifestyles, creating an urgent need to re-evaluate the burden of these conditions. This study aimed to determine the prevalence and geographical distribution of refractive errors among elementary school children across six districts in Bali, Indonesia, during the post-pandemic period (2022–2023). Methods: A descriptive cross-sectional study was conducted using secondary data from the John Fawcett Foundation (JFF) school eye health screening program. The final analysis included 2,145 elementary school children (47.5% male, 52.5% female) from 13 schools across six districts in Bali, screened between January 2022 and December 2023. Visual acuity was measured using a Snellen chart, followed by non-cycloplegic autorefraction for all children failing the initial screening. Ametropia was defined based on established spherical equivalent and cylindrical thresholds. Prevalence was calculated for each district, and a Chi-square test was used to analyze the association with gender. Results: The overall prevalence of ametropia was 4.1% (88/2,145). Myopia was the most common refractive error, accounting for 58 cases (2.7% of all children), followed by astigmatism with 22 cases (1.0%) and hypermetropia with 8 cases (0.4%). Significant geographical disparities were observed, with prevalence rates ranging from a low of 1.8% in Tabanan district to a high of 6.9% in Denpasar district. The highest prevalence rates were found in the urban and semi-urban districts of Denpasar (6.9%) and Buleleng (6.3%). There was no statistically significant association between gender and the presence of refractive error (p=0.115). Conclusion: The post-pandemic prevalence of refractive errors in this large cohort of Balinese schoolchildren reveals a significant public health challenge defined by a sharp urban-rural divide. The concentration of refractive errors, primarily myopia, in urban centers like Denpasar points to the profound impact of environmental and lifestyle factors on visual development. This evidence provides a clear mandate for the strategic deployment of targeted pediatric eye care resources to the island's most affected communities, ensuring the early detection and management necessary to prevent lifelong visual impairment and secure the future well-being of Bali's next generation.